Effective treatment of steroid and therapy-refractory acute graft-versus-host disease with a novel mesenchymal stromal cell product (MSC-FFM) - Bader, Peter; Greil, Johann (Bone marrow transplantation, 2018)
The inability to generate mesenchymal stromal cells (MSCs) of consistent potency likely is responsible for inconsistent clinical outcomes of patients with aGvHD receiving MSC products. We developed a novel MSC manufacturing protocol characterized by high in vitro potency and near-identity of individual doses, referred to as “MSC-Frankfurt am Main (MSC-FFM)”. Herein, we report outcomes of the 69 patients who have received MSC-FFM. These were 51 children and 18 adults with refractory aGvHD grade II (4%), III (36%) or IV (59%). Patients were refractory either to frontline therapy (steroids) (29%) or to steroids and 1-5 additional lines of immunosuppressants (71%) were given infusions in four weekly intervals. The day 28 overall response rate was 83%; at the last follow-up, 61% and 25% of patients were in complete or partial remission. The median follow-up was 8.1 months. Six-month estimate for cumulative incidence of non-relapse mortality was 27% (range, 16-38); leukemia relapse mortality was 2% (range, 0-5). This was associated with a superior six-month overall survival (OS) probability rate of 71% (range, 61-83), compared to the outcome of patients not treated with MSC-FFM. This novel product was effective in children and adults, suggesting that MSC-FFM represents a promising therapy for steroid refractory aGvHD.
Gesehen am 02.03.2020